Pembangunan untuk semua : mengelola pembangunan regional la SBY - Wanggai, Velix Vernando, 1972- ([Jakarta] : Indomultimedia, 2012)
Social and economic development in Indonesia under President Susilo Bambang Yudhoyono.
Keywords: Economic development -- Indonesia; Indonesia -- Economic policy; Indonesia -- Economic conditions -- 1945-